Persistent organic pollutants in wood fiber–contaminated sediments from the Baltic Sea - Dahlberg, Anna-Karin; Apler, Anna; Vogel, Lisa; Wiberg, Karin; Josefsson, Sarah (Journal of Soils and Sediments, 2020)
Abstract Purpose Many coastal areas in the Baltic Sea are contaminated with wood fiber and pollutants from pulp and paper industries. These anthropogenic, organic-rich, sediments (fiberbanks) have not been characterized and knowledge about their role as secondary sources for dispersal of persistent organic pollutants (POPs) is limited. Hence, the aim of this study was to elucidate the fate of POPs and the relationships between sorption ( K D and K TOC ), sediment type, and compound hydrophobicity ( K OW ) in fiber-contaminated sediments. Materials and methods Paired sediment and pore water samples ( n = 24 sites) from three fiber-contaminated areas, located in the Ångermanälven river estuary in northern Sweden, were analyzed for POPs (viz. PCBs, DDT, and HCB) in sediment types representing different fiber content (i.e., fiberbanks, fiber-rich sediments, and natural less fiber impacted sediments). The freely dissolved concentration in sediment pore water was determined by sediment-polyoxymethylene (POM) partitioning. Instrumental analysis was performed using gas chromatography coupled to a triple quadrupole mass spectrometer (GC-MS/MS). Results and discussion Higher levels of total organic carbon (TOC) were found in the fiberbank sediment (range 8.6–37%) than in fiber-rich sediment (range 2.0–6.5%) and more natural sediment (range 2.0–2.9%). The sediment concentrations of POPs (dry weight basis) were also found to be significantly ( p < 0.05) elevated in fiberbanks compared to the other sediment types. The fraction of DDD (48–66% of Σ 6 DDX) was larger in fiberbanks than in the other sediment types, likely due to anoxic conditions favoring reductive dechlorination of DDT. When sediment levels were normalized to TOC, HCB displayed similar levels across sediment type, suggesting a more diffuse source pattern than for PCB and DDT. Although significantly higher sorption ( K D ) of POPs was observed in fiberbanks, pore water levels were still elevated due to high bulk concentrations. Conclusions This study shows that fiberbanks are coastal hot spots for POPs in the Baltic Sea and that the levels are of ecotoxicological concern. Although the POPs are more strongly sorbed ( K D ) to this type of organic rich sediment, the high pore water concentrations in fiberbanks compared to the other sediment types investigated show that the risk of contaminant dispersal via pore water is elevated for fiberbanks.